Adapting ‘The Normal’ – Examining Relations between Youth, Risk and Accidents at Work - Nielsen, Mette Lykke (Nordic Journal of Working Life Studies, 2012)
People between 18 and 24 years of age are more exposed to accidents at work than anyone else. This article examines how safety is experienced and practiced among young employees. The aim of the article is to examine relations among youth, risk, and occupational safety. The article offers an insight into young employees’ narratives of risk situations at work. It examines the ways young employees in different organizational contexts talk about – and relate to – dangerous situations at work that they have experienced themselves. Safety is according to Silvia Gherardi considered as a product of situated ‘activity of everyday practices’ in organizations. Parallel to this, the article draws on Diane Vaughan’s theorizing about organizational production of ‘acceptable risk’ and organizational deviances in socially organized settings. The article shows how young employees position themselves – and are positioned – in organizations within different discourses of risk and safety because they are young and as a part of practicing youth.